GOC Touché = Touché. - Gespreks- en Onthaalcentrum (GOC) Aalst (Aalst : GOC, 1983)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijksRedactie : Hoogstraat 64-66, 9300 Aalst
Titel vanaf 01(1983-1984) 8 : Touché
Nederlands
Periodiek